ANALISIS PENGARUH INSTRUMEN MONETER SYARIAH TERHADAP PENYALURAN DANA KE SEKTOR USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI INDONESIA - Kharisma Rindang Sejati (Mandala, 2018)
Bank Indonesia as the authorized monetary institution formulated Islamic Bank Indonesia Certificate (abreviated as SBIS) as one of the islamic monetary instruments. The instrument plays pivotal role to transmit monetary policy to real sector. Monetary transmission occurred through cash transfer from Islamic Banking including financing for micro, small, and medium enterpries (MSME). This research aimed to analyze the influence of the islamic monetary instrument towards financial transfer to MSME. Data of Bank Indonesia, Cooperative Ministry and Statistical Agency was used during the period of January 2006 up to June 2015 and it analyzed with various techniques, such as Vector Error Corection Model (VECM), Impulse Response Function technique and Forecast Error Variance Decomposision (FEVD. UMKM financing, Profit and Loss Sharing (PLS), Margin, Consumer Price Index (CPI) and SBIS were applied as research variables. This study concluded SBSI has no significant impact to finance MSME of Bank Syari’ah. PLS and inflation contributed significantly to financial transfer of MSME and SBIS was not effective instrument to reduce inflation level.